Properties of D-Xylose Isomerase from Streptomyces albus - Sanchez, Sergio (1975)
A partially purified D-xylose isomerase has been isolated from cells of Streptomyces albus NRRL 5778 and some of its properties have been determined. D-Glucose, D-xylose, D-ribose, L-arabinose, and L-rhamnose served as substrates for the enzyme with respective K(m) values of 86, 93, 350, 153, and 312 mM and V(max) values measuring 1.23, 2.9, 2.63, 0.153, and 0.048 μmol/min per mg of protein. The hexose D-allose was also isomerized. The enzyme was strongly activated by 1.0 mM Mg(2+) but only partially activated by 1.0 mM Co(2+). The respective K(m) values for Mg(2+) and Co(2+) were 0.3 and 0.003 mM. Mg(2+) and Co(2+) appear to have separate binding sites on the isomerase. These cations also protect the enzyme from thermal denaturation and from D-sorbitol inhibition. The optimum temperature for ketose formation was 70 to 80 C at pH values ranging from 7 to 9. D-Sorbitol acts as a competitive inhibitor with a K(i) of 5.5 mM against D-glucose, D-xylose, and D-ribose. Induction experiments, Mg(2+) activation, and D-sorbitol D-sorbitol inhibition indicated that a single enzyme (D-xylose isomerase) was responsible for the isomerization of the pentoses, methyl pentose, and glucose.